2017
DOI: 10.3389/fmicb.2017.02256
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxigenicity and Antimicrobial Resistance of Staphylococcus aureus Isolated from Retail Food in China

Abstract: Staphylococcus aureus is one of the most common causes of zoonotic agent in the world, which are attributable to the contamination of food with enterotoxins. In this study, a total of 1,150 S. aureus isolates were cultured from 27,000 retail foods items from 203 cities of 24 provinces in China in 2015 and were test for antimicrobial susceptibility. Additionally, the role of the genes responsible for the staphylococcal enterotoxins (SEA to SEE), methicillin resistance (mecA) and the toxigenic capabilities were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
70
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 58 publications
12
70
2
Order By: Relevance
“…Most of the MRSA strains were resist to β-lactams and other antibiotics which showed 77.4% (48/62) were resistant to more than 10 antibiotics. This result as similar with the results of research by Wang et al ( 2017 ) and Hao et al ( 2015 ) in China. In fact, the prevalence of MRSA varies greatly by geographical location in retail meats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most of the MRSA strains were resist to β-lactams and other antibiotics which showed 77.4% (48/62) were resistant to more than 10 antibiotics. This result as similar with the results of research by Wang et al ( 2017 ) and Hao et al ( 2015 ) in China. In fact, the prevalence of MRSA varies greatly by geographical location in retail meats.…”
Section: Discussionsupporting
confidence: 93%
“…In China, (Xing et al, 2014 ) revealed that 98.4% of S. aureus isolates in ready-to-eat food were resist to more than one antimicrobial agent and 58.6% of isolates resist to more than three antimicrobials, while (Hao et al, 2015 ) found that 35.9% of S. aureus isolated from quick-frozen dumpling were resistant to less than or equal to 3 kinds of drugs. In Wang et al ( 2017 ) reported that 97.6% of S. aureus isolates from retail food showed resistance in one or more antimicrobial agents. The prevalence of resistance to clindamycin, gentamicin, penicillin, erythromycin, tetracycline, and ciprofloxacin is in agreement with our data.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by many authors, raw milk has been identified as a source of MRSA demonstrating the potential food safety of contaminated milk and dairy products entering the human food chain (Carfora et al 2015;Caruso et al 2016;Parisi et al 2016;Basanisi et al 2017;Giaciniti et al 2017;Papadopoulos et al 2019b;Titouche et al 2019). However, MRSA was also isolated in meat (De Boer et al 2009;Hanson et al 2011;Thapaliya et al 2017;Tang et al 2017) and from ready to eat products (Wang et al 2017;Islam et al 2019). To date, a great number of studies reported the isolation of MRSA from livestock, wild animals and derived foods, both raw and ready to eat, as well as from professionals working in animal husbandry or the food production chain settings (Sergelidis and Angelidis 2017).…”
Section: Discussionmentioning
confidence: 86%
“…In recent years, the spread of antibiotic resistance among strains of S. aureus is of great public and clinical concern in the treatment of staphylococcal infections (Shankar, 2012 ). Many researchers have reported resistance strains of S. aureus isolates from various food samples in different countries (Argudín et al, 2012 ; Yang et al, 2016b ; Wang et al, 2017 ). In the current study, 76.7% of vegetable S. aureus isolates (23/30) were resistant or intermediate resistant to more than three tested antibiotics classes, of which 9 isolates were resistant to more than 10 antibiotics.…”
Section: Discussionmentioning
confidence: 99%